Social health status in iran: an empirical study. - Mostafa Amini Rarani; Hassan Rafiye; Esmaeil Khedmati Morasae (Tehran University of Medical Sciences, 2013)
As social health is a condition-driven, dynamic and fluid concept, it seems necessary to construct and obtain a national and relevant concept of it for every society. Providing an empirical back up for Iran's concept of social health was the aim of the present study.This study is an ecologic study in which available data for 30 provinces of Iran in 2007 were analyzed. In order to prove construct validity and obtain a social health index, an exploratory factor analysis was conducted on six indicators of population growth, willful murder, poverty, unemployment, insurance coverage and literacy.Following the factor analysis, two factors of Diathesis (made up of high population growth, poverty, low insurance coverage and illiteracy) and Problem (made up of unemployment and willful murder) were extracted. The diathesis and problem explained 48.6 and 19.6% of social health variance respectively. From provinces, Sistan & Baluchistan had the highest rate of poverty and violence and the lowest rate of literacy and insurance coverage. In terms of social health index, Tehran, Semnan, Isfahan, Bushehr and Mazandaran had the highest ranks while Sistan and Baluchistan, Lurestan, Kohkiloyeh and Kermanshah occupied the lowest ones.There are some differences and similarities between Iranian concept of social health and that of other societies. However, a matter that makes our concept special and different is its attention to population. The increase in literacy rate and insurance coverage along with reduction of poverty, violence and unemployment rates can be the main intervention strategies to improve social health status in Iran.